수술실 간호사가 지각하는 간호조직문화 유형, 셀프리더십 및 소진 간의 관계 - 임민경(Im, Minkyung); 성영희(Sung, Young-Hee); 정정희(Jung, Junghee) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2017)
Purpose: This study was designed to assess the types of nursing organizational culture, and degree of self-leadership and burnout as perceived by perioperative nurses, and to identify correlations between these variables. Methods: Participants were 155 nurses from 3 tertiary hospitals in Seoul and data were analyzed using descriptive statistics, ANOVA, Scheffe, and Pearson correlation coefficient. Results: In the types of nursing organizational culture, the mean score for hierarchy-oriented culture was 3.57, and for self-leadership, 3.61 and for burnout, 2.87. In the relationship between the types of nursing organizational culture, self-leadership and burnout, relation-oriented culture (r=.24, p<.01), innovation-oriented culture (r=.23, p<.01) and task-oriented culture (r=.22, p<.01) had a slight positive correlation with self-leadership in that order. The innovation-oriented culture (r=-.29, p<.01) and relation-oriented culture (r=-.42, p<.01) among the types of nursing organizational culture showed a negative correlation with burnout while the hierarchy-oriented culture (r=.28, p<.01) showed a positive correlation with burnout. Self-leadership showed a negative correlation with burnout (r=-.42, p<.01). Conclusion: The results show that nurses in operating rooms have a high awareness of hierarchy-oriented culture that affects burnout in a negative way while having a low awareness of relation-oriented culture that has a positive influence on burnout.